Effectiveness analysis of stand-alone toxicity removal system - Mohd. Hudzari, Haji Razali; Nashriyah, Mat; Wan Musa, Wan Muda; Abd Jamil, Zakaria (2013)
Dioscorea hispida Dennts tubers are highly toxic and can only be eaten after the elimination of toxins. In the present work an attempt has been done to develop stand alone toxin removal machine which is used to remove (Dioscorine) in the tuber by using modern method. Statistical analysis from the results obtained concluded that the toxic is fully removed from blended tuber after 7 hours of machine operation and water usage is about 60 liters. Hence, This machine can work as stand alone which can replace traditional method for removing toxic content of tubers and and can owned at home for daily traditional food processing.